The impact of culturally responsive project-based learning with flipbook stories on elementary students’ speech-writing skills - Inggriyani, Feby; Putri, Sarah Anida (Institut Agama Islam Negeri Kendari, 2026)
This study examined the effect of a Project-Based Learning (PjBL) model integrated with a Culturally Responsive Teaching (CRT) approach and flipbook Hero Stories on elementary students’ speech-writing ability. A quasi-experimental design was applied to 66 fifth-grade students divided equally into experimental and control groups through total sampling. Data were analyzed using the Mann–Whitney U test, gain score analysis, and effect size calculation to identify differences in learning outcomes and control baseline variation. The findings revealed that the experimental group achieved significantly higher post-test scores than the control group (p < 0.001), with a large effect size (1.72). The integration of PjBL, CRT, and interactive digital media was shown to improve students’ engagement, creativity, and understanding of speech-text structure by connecting learning materials with students’ cultural backgrounds and experiences. These findings highlight the potential of culturally responsive, project-oriented instruction to strengthen writing skills in elementary education.